Survey of cataract surgeons' and nurses' attitudes toward operating room waste - Chang, David F; Thiel, Cassandra L (Journal of cataract and refractive surgery, 2020)
In an online survey of more than 1300 cataract surgeons and nurses, 93% believed that operating room waste is excessive and should be reduced; 78% believed that we should reuse more supplies; 90% were concerned about global warming; and 87% wanted medical societies to advocate for reducing the surgical carbon footprint. The most commonly cited reasons for excessive waste were regulatory and manufacturer restrictions on reuse or multiple use of devices, supplies, and pharmaceuticals. More than 90% believed that profit, liability reduction, and failure to consider carbon footprint drive manufacturers to produce more single-use products; more than 90% want more reusable products and more regulatory and manufacturer discretion over when and which products can be reused. Assuming comparable cost, 79% of surgeons preferred reusable over disposable instruments. In order of decreasing consensus, most were interested in reusing topical and intracameral medications, phacoemulsification tips, irrigating solutions/tubing, blades, cannulas, devices, and surgical gowns.